2010
DOI: 10.1371/journal.pone.0010714
|View full text |Cite
|
Sign up to set email alerts
|

The Stem Cell Marker CD133 Associates with Enhanced Colony Formation and Cell Motility in Colorectal Cancer

Abstract: CD133 is a membrane molecule that has been, controversially, reported as a CSC marker in colorectal cancer (CRC). In this study, we sought to clarify the expression and role of CD133 in CRC. Initially the size of the CD133−expressing (CD133+) population in eight well-described CRC cell lines was measured by flow cytometry and was found to range from 0% to >95%. The cell line HT29 has a CD133+ population of >95% and was chosen for functional evaluation of CD133 after gene knockdown by RNA interference. A time c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 23 publications
(32 reference statements)
7
63
1
Order By: Relevance
“…The two subpopulations were maintained at an apparently stable ratio of about 40 to 60% (CD133 + vs. 18,22,23 For instance, the detectable CD133 with its specific antibody (AC133) was shown to vary in a cell cycle dependent manner in colon cancer and melanoma cell lines; 18 the closest data to ours are those showing that CD133 re-emerged in the purified CD133 -SW480 cells when persistently incubated in vitro. 23 In addition, the level of CD133 in cancer cells could be upregulated in hypoxia. 19 Those data, together with ours, collectively indicate that the CD133 -cells could indeed convert into the CD133 + cells, which has long been neglected.…”
Section: The Cd133mentioning
confidence: 48%
See 1 more Smart Citation
“…The two subpopulations were maintained at an apparently stable ratio of about 40 to 60% (CD133 + vs. 18,22,23 For instance, the detectable CD133 with its specific antibody (AC133) was shown to vary in a cell cycle dependent manner in colon cancer and melanoma cell lines; 18 the closest data to ours are those showing that CD133 re-emerged in the purified CD133 -SW480 cells when persistently incubated in vitro. 23 In addition, the level of CD133 in cancer cells could be upregulated in hypoxia. 19 Those data, together with ours, collectively indicate that the CD133 -cells could indeed convert into the CD133 + cells, which has long been neglected.…”
Section: The Cd133mentioning
confidence: 48%
“…First, the data of ours and the reported 23 showed that only a small fraction of the CD133 + cells or the CD133 -cells could change into the opposite and that there appear to exist some yet-to-beclarified balance mechanisms to maintain those two types of the cells at a proper, apparently stable proportion according to different kinds of tumor cells. The expression of CD133 in a mixed population of the CD133 + cells and the CD133 -cells is likely to be in a dynamic, changeable state though with an apparently stable proportion.…”
Section: Methodsmentioning
confidence: 63%
“…43 Furthermore, CD133 knockdown was shown to result in greater susceptibility to staurosporine-induced apoptosis and reduced cell motility. 29 Taken together, these findings suggested that CD133 has a role in response to treatment and/or CSC behavior of HT29 cells. A literature review, however, also indicated considerable differences in CD133 expression levels in HT29 cultures in various laboratories.…”
Section: Discussionmentioning
confidence: 80%
“…18,22,[26][27][28][29][30] Because the fluorescence-staining procedure critically impacts the ), whereas 90.9 ± 6.4% of exponentially growing HT29 cells in serum-containing DMEM clearly expressed CD133 on the cell surface. The resulting sort layout and a representative reanalysis after separation of the subpopulations are shown in Figure 1b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation